2018
DOI: 10.3324/haematol.2018.203919
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial of individualized treatment summary and survivorship care plans for hematopoietic cell transplantation survivors

Abstract: Survivorship Care Plans (SCPs) may facilitate long-term care for cancer survivors, but their effectiveness has not been established in hematopoietic cell transplantation recipients. We evaluated the impact of individualized SCPs on patient-reported outcomes among transplant survivors. Adult (≥18 years at transplant) survivors who were 1-5 years post transplantation, proficient in English, and without relapse or secondary cancers were eligible for this multicenter randomized trial. SCPs were developed based on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
44
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(45 citation statements)
references
References 56 publications
1
44
0
Order By: Relevance
“…24,25 Survivorship Care Plans Some data suggest that SCPs and treatment summaries improve outcomes, such as emotional concerns. 26,27 However, a randomized controlled trial (RCT) of 408 breast cancer survivors found no differences in patientreported outcomes, including cancer-specific distress, between patients who received a discharge visit and a care plan and those who received only a discharge visit. 28,29 Criticisms of this trial, including the relevance of its outcome measures, have been published.…”
Section: Care Coordinationmentioning
confidence: 99%
See 1 more Smart Citation
“…24,25 Survivorship Care Plans Some data suggest that SCPs and treatment summaries improve outcomes, such as emotional concerns. 26,27 However, a randomized controlled trial (RCT) of 408 breast cancer survivors found no differences in patientreported outcomes, including cancer-specific distress, between patients who received a discharge visit and a care plan and those who received only a discharge visit. 28,29 Criticisms of this trial, including the relevance of its outcome measures, have been published.…”
Section: Care Coordinationmentioning
confidence: 99%
“…Another RCT examined the mailing of a personalized SCP, which was designed with qualitative input of hematopoietic cell transplant survivors and briefly reviewed in a telehealth call by a trained nonprofessional. 27 The study randomly assigned 458 hematopoietic cell transplant survivors 1 to 5 years after transplant to receive the SCP or delayed SCP. After 6 months, the SCP recipients reported reduced cancerspecific distress and improved general mental health, although they did not report higher levels of confidence in survivorship information when compared with the delayed care plan recipients as hypothesized.…”
Section: Care Coordinationmentioning
confidence: 99%
“…Patients reported cancer-related distress using the 23-item Cancer and Treatment Distress (CTXD) inventory, a PRO measure previously used in HCT survivors [46][47][48]. Possible mean CTXD scores range from 0 to 3, where higher CTXD scores indicate higher distress.…”
Section: Study Measures Of Interestmentioning
confidence: 99%
“…Online programs are an attractive option for HCT survivors as many live far from their transplant center, and many go online seeking information [7][8][9][10]. Survivorship care plans (SCPs), currently recommended for all cancer survivors, are another way to help HCT survivors meet their healthcare needs [11][12][13]. SCPs should include information on (1) the underlying disease, treatments and their potential long-term or late effects, (2) rationale for and schedule of screening and preventive care evaluations, (3) recommendations about lifestyle practices, and (4) information to facilitate communication between health care providers [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…In a previous work by our group directed at adult HCT survivors in the United States (US), an individualized SCP for post-HCT care was developed in print format using feedback from patients, caregivers, and health care providers [14]. In a multi-center prospective, randomized control trial (RCT), it was effective in reducing cancer and treatment distress and improved the mental health domain of quality of life [13]. An internet-based intervention, INSPIRE (INternet-based Survivorship Program with Information and Resources), was also tested in an RCT, and had a marginal benefit in alleviating distress in an intent-to-treat analysis, although a significant effect on relieving distress in those who logged into the program [15,16].…”
Section: Introductionmentioning
confidence: 99%